Development of an integrated information storage of the system of the state accounting and control of radioactive substances and radioactive waste - M. S. Medvedkov; K. Yu. Kolybanov; S. N. Brykin; S. A. Yakushev (Тонкие химические технологии)
The article presents the stages of system analysis of the system of state accounting and control of radioactive substances and radioactive waste at the company FSUE «RosRAO» in the Central information-analytical center and shows the structure of the subsystem for information storage.